Is corruption an efficient grease? - Pierre-Guillaume Méon; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
This paper tests whether corruption may act as an efficient grease for the wheels of an otherwise deficient institutional framework. We analyze the interaction between aggregate efficiency, corruption, and other dimensions of governance for a panel of 54 developed and developing countries. Using three measures of corruption and five measures of other aspects of governance, we observe that corruption is consistently detrimental in countries where institutions are effective, but that it may be positively associated with efficiency in countries where institutions are ineffective. We thus find evidence of the grease the wheels hypothesis.
URN:NBN:fi:bof-201408072094
Keywords: C33; K4; O43; O47; 330; governance; corruption; income; aggregate productivity; efficiency